Can Training Enhance Adoption, Knowledge and Perception of Organic Farming Practices? Evidence from a Randomized Experiment in Indonesia - Michael Grimm; Nathalie Luck (Institute of Labor Economics (IZA), 2020)
In many parts of the world, several decades of intensively applying Green Revolution technologies came at environmental costs, i.e. degraded water and soil quality as well as a loss of biodiversity. This has led to an increased interest in alternative farming systems such as organic farming, which is commonly perceived as more sustainable. Despite many initiatives to promote organic farming, it remains a marginal activity in many countries. Widespread uptake of organic farming requires a better understanding of the drivers for and barriers to its adoption. Previous studies highlighted information as an important driver of agricultural technology adoption. Yet, despite the variety of programs studied, little is known about the role of removing information constraints in the context of organic farming. In this paper, we focus on the role of information provision and training as one driver for the adoption of organic farming practices in Indonesia. We use a randomized controlled trial (RCT) to identify the impact of a three-day hands-on training in organic farming on smallholder farmers' adoption and knowledge of such practices as well as on their perception towards organic farming. We find that the training intervention had a positive and statistically significant effect on the use of organic inputs. We further find positive and statistically significant treatment effects with respect to knowledge about and perception of organic farming. Overall, our findings suggest that intense training is a promising instrument to increase the uptake of organic farming.
Keywords: C93; O12; O33; Q12; Q16; 330; organic farming; technology adoption; RCT; Indonesia